Thermal modeling techniques designed for high-speed directed energy deposition coatings - Shiho TAKEMURA; Yuichiro MIYATA; Yoko HIRONO; Yasuhiro KAKINUMA (Journal of Advanced Mechanical Design, Systems, and Manufacturing)
High-speed directed energy deposition (DED) offers advantages such as efficiency, thin coating layers, and reduced heat-affected zones, making it ideal for repairs and coating on existing parts across various industries. In the DED process, various deposition parameters are included and affect the thermal history. Moreover, a thermal history significantly affects the deposit's mechanical properties by varying metallographic structure. Therefore, thermal simulations of DED are highly demanded due to the time and cost challenges associated with experimenting across different process parameters. However, thermal simulations of DED have difficulties because of the process by which material and heat source are supplied from time to time to the melt pool. Many studies have been conducted on thermal simulations of DED, however, few studies focus on high-speed DED coating. Therefore, this research develops the thermal simulation techniques for high-speed DED coating by exploring five simple methods for element addition and heat input. The geometry of the workpiece model was simplified to reduce the simulation cost. Using the Ansys Parametric Design Language (APDL) software and the simplified workpiece model, we conducted thermal simulations and validated them against experimental data acquired from high-speed imaging and two-color temperature measurements. Through these methods, the study proposed the temperature comparison method of experiment and simulation results and identified the suitable method for element addition and heat input in high-speed DED coating that closely replicates the actual temperature within the coating layer. This method reduces the need for finer mesh, effectively lowering computational costs while maintaining accuracy. The findings provide insights into practical simulation practices for DED and contribute to enhancing parameter validation in additive manufacturing simulations, supporting further development in high-speed DED coating technology.